Foliar epidermal micro-morphology of selected brinjal varieties: A study on leaf surface characteristics - Soumyamol, Nizarudeen; Sheeba, Muhammed Jameelabeevi (Current Botany, 2024)
Studies on the leaf epidermal morphological characteristics were conducted on the three varieties of brinjal (Solanum melongena L.) belonging to the family Solanaceae. The varieties used in the study were Bhavani Gold, Purple Round and Haritha. Fresh mature brinjal leaves were randomly selected from the three experimental genotypes, and the foliar epidermal features were studied by using light microscopy and SEM imaging. Measurements were taken with an ocular and stage micrometer using 10X and 40X magnifications. The photographs were taken from mounted slides. The stomatal count and each measurement represent the average of ten readings. The upper and lower epidermal surfaces of leaf were studied for stomatal features including, stomatal distribution, stomatal type, stomatal index, stomatal pore length, stomatal pore width, guard cell length, guard cell width, subsidiary cell length and width, epidermal cell type, epidermal cell length and width, trichome type, trichome length and width. Amphistomatous, anisocytic, and with more stomata on the lower epidermal surface than the upper epidermal surface were present in all leaf varieties. On the leaves, the abaxial stomatal index ranged from 68.19 mm-2 (Bhavani Gold) to 56.67 mm-2 (Purple Round) to 58.8 mm-2 (Haritha). While on the adaxial surface, it varied from 59.67 mm-2 (Bhavani Gold), 53.46 mm-2 (Purple Round) and 56.67 mm-2 (Haritha). The three varieties of this study exhibited similarities in the pattern of epidermal cell on the adaxial and abaxial surfaces and were irregular in shape. Among the three varieties epidermal cell become irregular in outline and trichomes were present on both leaf surfaces. It becomes stellate, non-glandular, glandular and 8-12 in number. The highest trichome length was obtained in Bhavani Gold (63 μm) followed by Haritha (57.5 μm) and Purple Round (43 μm) on the upper epidermis. On the lower epidermal region maximum length was obtained in Bhavani Gold (65.5 μm) followed by Haritha (53 μm) and Purple Round (44 μm).